The Influence of Adaptive Capacity and Participatory Governance on Community Preparedness for Flood Disasters - Rr Nafisa Alya Fathinnisa; Dewi Larasati; Hanson Endra Kusuma; Wahyuni Zahrah; Roiswahid Dimas Pangestu (Talenta Publisher, 2026)
Global climate change has increased the frequency and intensity of hydrometeorological disasters, particularly floods in urban areas of Indonesia. High settlement density, inadequate drainage systems, and limited community preparedness further exacerbate flood vulnerability. Although various flood mitigation strategies have been implemented, the relationship between mitigation effectiveness, perceptions of community participation, and community readiness remains insufficiently examined through quantitative approaches, limiting the development of effective community-based interventions. This study analyses the influence of flood mitigation efforts—specifically adaptive capacity—and perceptions of community participation on community readiness, measured through risk literacy and structural preparedness. A mixed-methods approach was applied, combining factor analysis to identify latent dimensions and linear regression to examine relationships between variables. Data were collected from questionnaires administered to residents with prior flood experience and analysed using JMP software. The results indicate that Adaptive Capacity has a positive and significant effect on Structural Preparedness (β = 0.3930; p < 0.0001) and Risk Literacy (β = 0.3765; p < 0.0001). The Governance dimension of participation also shows a positive and significant influence on Structural Preparedness (β = 0.2499; p = 0.0170). In contrast, the Environmental Action dimension exhibits a negative and significant relationship with Risk Literacy (β = –0.3070; p = 0.0019). These findings suggest that community readiness is more strongly influenced by adaptive capacity and participatory governance than by physical environmental actions alone. The study highlights the need to integrate technical and social approaches and to strengthen risk literacy to enhance long-term community resilience to flood risks.